2018
DOI: 10.1021/acs.analchem.7b05102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Identity and Mechanism of Action and Formation of a Cell Growth Inhibitory Compound from Polycarbonate Flasks

Abstract: This paper reports the chemical identity and mechanism of action and formation of a cell growth inhibitory compound leached from some single-use Erlenmeyer polycarbonate shaker flasks under routine cell culture conditions. Single-use cell culture vessels have been increasingly used for the production of biopharmaceuticals; however, they often suffer from issues associated with leachables that may interfere with cell growth and protein stability. Here, high-performance liquid-chromatography preparations and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…If the assay for residual host cell DNA is designed to only test enough material to be able to meet the specification, it is possible that information about process variability contained in the sample matrix might be lost. Finally, this work provides another example demonstrating that there are many raw materials used in the production and purification of protein therapeutics, any of which could serve as the source of an unknown impurity 19–21 or leachable compound 22,23 that may impact process performance or product quality. Even the most robust raw material control strategies may not be able to catch such unexpected issues, highlighting the need for robust complementary quality systems for control and monitoring of product quality and investigation and response to deviations.…”
Section: Discussionmentioning
confidence: 96%
“…If the assay for residual host cell DNA is designed to only test enough material to be able to meet the specification, it is possible that information about process variability contained in the sample matrix might be lost. Finally, this work provides another example demonstrating that there are many raw materials used in the production and purification of protein therapeutics, any of which could serve as the source of an unknown impurity 19–21 or leachable compound 22,23 that may impact process performance or product quality. Even the most robust raw material control strategies may not be able to catch such unexpected issues, highlighting the need for robust complementary quality systems for control and monitoring of product quality and investigation and response to deviations.…”
Section: Discussionmentioning
confidence: 96%
“…Oleamide, is one of the surfactant, has a variety of industrial uses including as a slip agent, a lubricant, and a corrosion inhibitor [80]. Oleamide is known to be leached out of polypropylene plastics [81]. It is reported that, in rats, the oral LD50 of undiluted oleamide DEA was 12.4 mL/kg [82].…”
Section: Non-target Screeningmentioning
confidence: 99%
“…The second compound found to inhibit cell growth is 3,5-dinitro-bisphenol A (BPA), first reported in 2018 from polycarbonate shake flasks (111). Using water-based extraction studies, the authors showed that some polycarbonate flasks exhibit seeding density-dependent growth inhibition of CHO cells, with different CHO strains demonstrating varying sensitivities.…”
Section: Materials Sciencementioning
confidence: 99%